Overview Impact of Gadget on Mental Emotional Health of Preschool Age Children in Bukittinggi - Wati, Del Fatma; Putri, Meri Amelia (Journal of Health Science and Medical Therapy, 2025)
Various factors influence the mental and emotional development of preschool children. Currently, preschool children are often exposed to gadgets. Children are usually more interested in gadgets than their peers or family. The success of the emotional development of preschool children should be optimized by managing and recognizing their emotions in their social environment. This research explores gadgets' impact on emotional and mental health in preschool-age children in Bukittinggi using a qualitative research method with a phenomenological approach. The informants of this study were taken by purposive sampling, totaling 6 people. The result of the analysis contained several themes, namely, 1) lack of attention and supervision in playing with gadgets, 2) bad behavior due to gadgets, and 3) psychological changes in children. Conclusion This study shows that the use of gadgets by preschool children should be controlled and accompanied. Parents can divert attention from playing gadgets by introducing traditional games because they can stimulate the development of emotional skills in children.